2013
DOI: 10.1002/jmv.23703
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high‐risk human papillomaviruses in fresh breast cancer samples using the hybrid capture 2 assay

Abstract: The etiology of breast cancer remains unknown and the role of human papillomavirus (HPV) in breast carcinogenesis is controversial. This study investigated the prevalence of high-risk HPV infections in Chinese women with breast cancer and the possible relationship between high-risk HPV infection and the clinicopathological characteristics of breast cancer. Tumor cells from 224 fresh breast cancer samples and 37 fresh breast fibroadenomas were collected for hybrid capture 2 (HC2) assay. HC2 was the only techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…Most of the published studies do not follow a precise methodology, and the screening criteria used are very heterogeneous. Some studies only consider juvenile malignancies [34], while others include inflammatory breast cancer tissues [48, 49], triple-negative tumors [50], medullary malignancies [51], metaplastic breast cancer [52], papillary lesions [20, 53], Paget’s disease [54], or carcinoma in situ [9, 24, 25, 36, 41, 55–60]. In addition, no standards are used in selecting the molecular technique to screen for viruses, implying the potential detection of different viral serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the published studies do not follow a precise methodology, and the screening criteria used are very heterogeneous. Some studies only consider juvenile malignancies [34], while others include inflammatory breast cancer tissues [48, 49], triple-negative tumors [50], medullary malignancies [51], metaplastic breast cancer [52], papillary lesions [20, 53], Paget’s disease [54], or carcinoma in situ [9, 24, 25, 36, 41, 55–60]. In addition, no standards are used in selecting the molecular technique to screen for viruses, implying the potential detection of different viral serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In total, only 7 studies have published HPV status in BC and non-cancer controls with case-control design in female Chinese [ 34 , 38 , 40 , 41 , 45 , 49 , 50 ]. In 1992, Yu et al reported 15 of 34 BC infected with HPV 33 and both 2 benign and atypical ductal hyperplasia showed negative HPV infection using TS PCR and dot blot hybridization which could detect HPV 16, 18 and 33 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The URR (upstream regulatory region) was also used [43], and primers for the E1 region [64, 67], microarray [56], multiplex PCR [78], hybrid capture [74], or genotyping kits directly [71]. …”
Section: Resultsmentioning
confidence: 99%
“…Another evaluated the presence of HPV in milk epithelial cells, but used a PCR technique [72]. Yet another investigated HPV by hybrid capture in intraoperative tumor smears [74]. …”
Section: The Role Of Cytology In Hpv-related Breast Cancermentioning
confidence: 99%